Demographic, Clinical and Genetic Characteristics of Child Gaucher Disease Patients in Russia: Pediatric Register Data - G. B. Movsisyan; O. S. Gundobina; L. S. Namazova-Baranova; K. V. Savostyanov; A. N. Pushkov; V. V. Chernikov; N. N. Mazanova; A. M. Romanyuk; V. I. Smirnov (Педиатрическая фармакология)
Background: Registers are an effective tool for tracing the dynamics of patients with rare pathologies.Objective: Our aim was to examine the demographic, clinical and genetic features of child Gaucher disease patients in Russia.Methods: We held a retrospective survey of the pediatric register data with regard to children suffering from Gaucher disease. The period of data accounting was from 2006 to 2016.Results: 115 children with Gaucher disease aged from 3 months to 17 years (the median age of diagnosis is 5 years) were registered; 62 them (53.9%) are girls. The prevalence of the disease was 0.32 cases for 100,000 children. 95 (82.6%) children had 1st type of Gaucher disease, 6 (5.2%) — 2nd, and 1 (12.2%) — 3rd. Maximum morbidity was in Central (27; 23.5%) and Volga (27; 23.5%) Federal Districts; minimal — in the Far East (3; 2.6%). By the time of diagnosis all the patients were suffering from splengomegaly. The genotype and phenotype correlations in 90 children with Gaucher disease were as follows: in case of 1st type (n = 77), in 21 (27.3%) cases, the p.N370S/р.L444P genotype was set, in 12 (15.6%) — the р.N370S/other mutation; in case of 2nd and 3rd types, in 13 children with neuropathic forms, in 9 (62.9%) cases — the p.L444P/p.L444P, in 3 (231%) — the p.L444P/p. D409H. The rest of genotypes were presented by other mutations, 13 of which were revealed for the first time. The p.W223R (p.W184R) mutation is specific for Russian patients. Enzyme replacement therapy was carried out for 109 patients (94.8%): in 105 (96.3%) children (1st and 3rd types of Gaucher disease) with imiglucerase, in 4 (3.7%) children with 1st type — with velaglucerase alfa. Pathogenetic treatment stops the main symptoms in most patients.Conclusion: The pediatric Gaucher disease register allows to systemize the data concerning the disease course in children and optimizing the approaches to its monitoring in Russia.